Syndrome of cerebellar ataxia and hypogonadotrophic hypogonadism: evidence for pituitary gonadotrophin deficiency. Issue 3 (March 1989) - Fok, A C; Wong, M C; Cheah, J S
Abstract : Familial cerebellar ataxia with hypogonadotrophic hypogonadism is a rare condition. Two affected siblings in a sibship of three were studied and found to have low plasma gonadotrophin levels. No rise in gonadotrophin levels was demonstrable after repeated stimulation with LHRH. The pattern of TSH and prolactin responses to TRH stimulation suggest hypothalamic dysfunction. The results clearly identify the cause of hypogonadism to be due to a defect in production or release of gonadotrophins by the pituitary gland and suggest that hypogonadism is part of a greater endocrine disturbance involving both the hypothalamus and pituitary.